2009
DOI: 10.1080/00048670802607188
|View full text |Cite
|
Sign up to set email alerts
|

Psychotic-Like Experiences in a Community Sample of Adolescents: Implications for the Continuum Model of Psychosis and Prediction of Schizophrenia

Abstract: Given that the different subtypes had varying associations with current difficulties it is suggested that not all subtypes confer the same risk for onset of psychotic disorder and poor outcome. Bizarre Experiences, Perceptual Abnormalities and Persecutory Ideas may represent expressions of underlying vulnerability to psychotic disorder, but Magical Thinking may be a normal personality variant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
296
12
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 314 publications
(339 citation statements)
references
References 76 publications
(85 reference statements)
30
296
12
1
Order By: Relevance
“…Psychotic experiences are reasonably common in the general population (van Os et al, 2009), especially in adolescents (Kelleher et al, 2012;Scott et al, 2009;Yung et al, 2009), with one study finding that between .09 and 8% of a general population sample of adolescents met criteria for a risk syndrome, depending on varying disability criteria (Kelleher et al, 2012). Extending early detection to these populations (e.g., by screening for psychotic experiences in schools or over the internet) may identify a large number of young people, many with transient psychotic experiences, most of whom are not distressed by or seeking help for these experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Psychotic experiences are reasonably common in the general population (van Os et al, 2009), especially in adolescents (Kelleher et al, 2012;Scott et al, 2009;Yung et al, 2009), with one study finding that between .09 and 8% of a general population sample of adolescents met criteria for a risk syndrome, depending on varying disability criteria (Kelleher et al, 2012). Extending early detection to these populations (e.g., by screening for psychotic experiences in schools or over the internet) may identify a large number of young people, many with transient psychotic experiences, most of whom are not distressed by or seeking help for these experiences.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 19 studies met criteria for inclusion -5 interview studies (Horwood et al, 2008, Kelleher et al, 2008, Kelleher et al, In Press, Polanczyk et al, 2010, Poulton et al, 2000 and 14 self report questionnaire studies (Barragan et al, 2011, De Loore et al, 2011, Dhossche et al, 2002, Kelleher et al, In Press, Kinoshita et al, 2011, Lataster et al, 2006, Scott et al, 2009a, Scott et al, 2009b, Wigman et al, 2011, Yoshizumi et al, 2004, Yung et al, 2009) (see Table 1). …”
Section: Resultsmentioning
confidence: 99%
“…More recently, evidence has been emerging that the clinical significance of psychotic symptoms extends beyond psychosis, with a number of research groups finding that young people who endorse questionnaire items on psychotic symptoms are also more likely to endorse symptoms of non-psychotic psychopathology, especially symptoms of depression (Hanssen et al, 2003, Johns et al, 2004, Kelleher et al, In Press, Nishida et al, 2008, Polanczyk et al, 2010, Scott et al, 2009b, Varghese et al, 2011, Wigman et al, 2011, Yung et al, 2009.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, this rate is significantly better than those reported in some previous community-based studies involving samples of adolescents from other countries. For example, Yung et al (2009) reported a 19.7 % consent rate with a community sample of Australian adolescents (mean age=15.64 years). Third, this study did not consider the misattribution of facial expressions.…”
Section: Strengths and Limitationsmentioning
confidence: 99%